2021
DOI: 10.1371/journal.pone.0250920
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on respectful maternity care in Sri Lanka: Study protocol for a mixed-methods study of patients and providers

Abstract: Background Over the past few decades, interest in providing and measuring Respectful Maternity Care (RMC) has increased markedly. Sri Lanka is reportedly shown to have better maternal health statistics and studies on quality improvement are lacking in this unique population. We aim to describe healthcare providers’ perceptions and women’s expectations, perceptions and their gaps in service provision regarding RMC in Sri Lanka. Methods A descriptive cross-sectional study with a mixed-methods approach comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…It deters women from using health care facilities for the subsequent continuum of maternity care, thus deteriorating maternal and neonatal health outcomes in low-resource settings. [18][19][20][21] Evidence from SSA countries has reported that around 44% of women had faced D&A during childbirth. 22 In Ethiopia, there were abundant reports of D&A treatment during labor in health facilities ranging from 67% to 98%.…”
Section: Introductionmentioning
confidence: 99%
“…It deters women from using health care facilities for the subsequent continuum of maternity care, thus deteriorating maternal and neonatal health outcomes in low-resource settings. [18][19][20][21] Evidence from SSA countries has reported that around 44% of women had faced D&A during childbirth. 22 In Ethiopia, there were abundant reports of D&A treatment during labor in health facilities ranging from 67% to 98%.…”
Section: Introductionmentioning
confidence: 99%
“…The approximate annual delivery rate in CSHW is 11000 livebirths and that of DSHW is 8000. DSHW and CSHW are the first maternity hospitals situated in Sri Lanka and that they are considered model institutions [ 15 , 16 ].…”
Section: Main Textmentioning
confidence: 99%
“…[ 3 ] Despite the international laws upholding the pregnant women’s right to respectful maternal care (RMC), there are numerous reports of abuse, mistreatment, and neglect of the pregnant woman during the entire pregnancy cycle, especially in low- and middle-income countries (LMIC). [ 4 5 ] Such treatment violates women’s rights to RMC, threatens their rights to life, health, bodily integrity, and freedom from discrimination, and deters them from seeking evidence-based institutional care. [ 6 ] A systematic review of obstetric violence in India indicates at least one instance of mistreatment.…”
Section: Introductionmentioning
confidence: 99%